Assessment innovation using quizizz paper mode in PAI learning - Arizky Damayanti; Fadilah Nur Barokah; Bakti Fatwa Anbiya (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
With the development of the times, more and more advanced information technologies have emerged. One sign of the advancement of information technology is the use of various innovative applications, especially in the educational aspect. Most educators still do not understand the existence of this innovative application, this is the driving reason behind this research. This study aims to describe the use of Paper Mode Quizizz innovation in PAI learning assessment. The approach in this study is a qualitative approach using the literature study method. Data collection techniques by collecting and analyzing from various articles and images and video tutorials. The quizizz application is a game-based learning application by conducting assessments using quizzes to make it more fun because there are elements of games in it. Paper Mode Quizizz is one of the features of the Quizizz platform in the form of quizzes using paper that can be done by students without using a smartphone device. The result of this study is that Paper Mode Quizizz as a learning assessment media can be an alternative for educators so that assessments can run interestingly, interactively, and meaningfully. In addition, this innovation is also a learning medium in the form of educational games that can increase student participation in learning.